Romania : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Romania. (IMF Staff Country Reports; Country Report ;, 2018)
This 2018 Article IV Consultation highlights that Romania recorded strong economic growth in 2017, with record low unemployment and an improving financial sector. Private consumption boosted by fiscal stimulus and wage increases led the strong growth, while investment lagged and structural reforms slowed. Public investment fell to a multi-year low in percent of GDP with a low absorption of European Union funds. Both the government deficit and current account deficit widened, respectively to 2.8 and 3.4 percent of GDP in 2017. Growth is expected to reach 5 percent in 2018-led again by continuing stimulus to private consumption from fiscal relaxation-and accompanied by a current account deficit and elevated inflation, even as monetary policy is tightened.